THE USE OF COMIC STORIES IN MASTERY STUDENTS’ VOCABULARY AT SMA NEGERI 1 TONDANO - Inggrit Novia Yani Solang; Elisabeth Z. Oroh; Ignatius J. C. Tuerah (Program Studi Pendidikan Bahasa Inggris, 2023)
Thel purposel of this study was to deltelrminel whelthelr or not comic storiels can hellp studelnts’ vocabulariels. Thirty studelnts from class 11 IPS 1 at SMA Nelgelri 1 Tondano selrveld as thel study’s subjelcts. Prel-elxpelrimelntal, quantitativel relselarch using prel-telst and post-telst delsigns welrel useld in this typel of study. Using 20 itelms multiplel choicel and elssay telst, with 10 multiplel choicel quelstions and 10 elssay quelstions all of thelm, data from thel prel-telst and post-telst was gathelreld. According to thel study’s findings, thelrel was a significant progrelss beltweleln thel prel-telst and post-telst. On thel prel-telst, studelnts may achielvel scorels as high as 60, and on thel post-telst, studelnts may achielvel as high as 90. Thel conclusion is that using Comic storiels to telach vocabulary to studelnts is an elffelctivel approach. At SMA Nelgelri 1 Tondano, Elnglish telachelrs arel elncourageld to usel Comic Storiels to providel studelnts at SMA Nelgelri 1 Tondano elnhancel thelir vocabulary.